2020
DOI: 10.1590/1983-40632020v5062546
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical effects of Lantana camara L. allelochemicals on the seed germination of Avena sativa L.

Abstract: Lantana camara (L.) is considered one of the main weeds of agricultural crops, and allelochemicals produced by this species may be a source for the development of natural herbicides. In this study, phytotoxic effects of L. camara aqueous extracts on seed germination and seedling growth of Avena sativa (L.) were assessed. The experimental design was completely randomized, in a 2 x 5 factorial scheme, with treatments resulting from two assays, testing five concentrations of the extract (0 %, 2.5 %, 5.0 %, 7.5 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The findings were in agreement with the who reported that Lantanacamera release certain secondary metabolites as phenolic acids (Narwal, 1994) or/and phytotoxic chemicals, called as allelochemicals. Such allelochemicals hampers the seed germination and seedling growth due to the suppression of cellular membrane developments and increase in the production of reactive oxygen forms (Gindri et al, 2020). According to Kong et al, (2006) Lantadene A and lantadene B were isolated from aqueous extracts of Lantana camara leaves as allelochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were in agreement with the who reported that Lantanacamera release certain secondary metabolites as phenolic acids (Narwal, 1994) or/and phytotoxic chemicals, called as allelochemicals. Such allelochemicals hampers the seed germination and seedling growth due to the suppression of cellular membrane developments and increase in the production of reactive oxygen forms (Gindri et al, 2020). According to Kong et al, (2006) Lantadene A and lantadene B were isolated from aqueous extracts of Lantana camara leaves as allelochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Hatata and El-Darier [ 37 ] found that the activity of APX was higher in wheat leaves when treated with Achillea santolina shoot extract. Gindri et al [ 38 ] also stated that Lantana camara L. increased the APX activity of the host plant ( Avena sativa L.) seedling. According to Ding et al [ 39 ], higher SOD activity was measured in garlic ( Allium sativum L.) root exudates treated with lettuce extract, which contradicts with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous leaf extracts of L. camara inhibited the germination of Lactuca sativa L. due to the suppression of cellular membrane developments and increase in the production of reactive oxygen forms [32]. Aqueous leaf extracts of L. camara suppressed the development of leaf buds of Eichhornia crassipes Mart., increased the decay, and caused necrosis of E. crassipes leaves.…”
Section: Extractmentioning
confidence: 97%